Optimalisasi Hasil Belajar IPAS Berbasis Project Based Learning: Penelitian Tindakan Kelas pada Siswa Kelas IV SD GP Berea Tondano - Lisa Aprisilia Mauru; Harol Reflie Lumapow; Deysti Trifena Tarusu (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to improve student learning outcomes in Natural and Social Sciences (IPAS), specifically on the topic of changes in the state of matter, by implementing the Project Based Learning (PjBL) model in Grade IV of SD GP Berea Tondano. The research followed a cyclical procedure consisting of planning, implementation, observation, and reflection. This study employed a classroom action research design and was conducted during the odd semester of the 2025/2026 academic year. Data were collected through observation, testing, and documentation techniques, with 15 fourth-grade students serving as the research subjects. The findings revealed significant improvements across teacher activity, student activity, and learning completeness. Teacher performance in managing instruction improved notably, with an average observation score of 73 (good) in Cycle I, rising to 93 (excellent) in Cycle II. Student engagement in the learning process likewise increased, from an average of 68.26 (good) in Cycle I to 86.53 (excellent) in Cycle II. Student learning completeness also showed marked progress, with the average score reaching 46.77 (satisfactory) in Cycle I and advancing to 100 (excellent) in Cycle II. These results demonstrate that the implementation of the Project Based Learning (PjBL) model is effective in enhancing both student creativity and learning outcomes on the topic of changes in the state of matter.